Cashew Culture and its Potentialities in Andhra Pradesh - Nagarathnam, S. (Indian Forester, 1958)
Cashewnut tree is an exotic, largely grown on west coast of India. It is a recognized dollar earner and an imperative need has arisen for its extensive cultivation. The Forest Department in Andhra Pradesh has taken to planting cashew on a large scale in the reserved forests of the State. Its technique is simple. It comes up best by direct sowings. However, casualities may be replaced by basket seedlings. In drought conditions, watering from wells ( doruvus) is considered necessary at least once in three days. Manuring is also provided. One or two weedings may be necessary in forests areas. In the second year also, manuring and watering are usually advantageous. No operations are necessary afterwards. The cashew tree begins to bear from 5th year and on an average a tree yields 15 lbs. per annum. The cost of cultivation does not exceed Rs. 50 per acre. The rawnuts are processed in local factories under various operations such as roasting, shelling, peeling and grading. They are finally packed in air-tight tins and exported. In reality, cashew cultivation is not merely an economic enterprise, but also an act of national importance, that goes to solve, in its own way, the twin problems of unemployment and earning dollars.